MiR-222-3p Aggravates the Inflammatory Response by Targeting SOCS1 to Activate STAT3 Signaling in Ulcerative Colitis - Xia, Fei; Bo, Wenxia; Ding, Jinli; Yu, Yanqiu; Wang, Jianning (Turkish Journal of Gastroenterology, 2022)
Background: Ulcerative colitis is characterized by relapsing inflammation in the gastrointestinal tract with limited treatment options. The aim of the present study was to assess the anti-inflammatory effect of Suppressor of cytokine signaling (SOCS1) on lipopolysac- charide-stimulated RAW264.7 cells and to investigate its potential mechanisms. Methods: The in vitro ulcerative colitis model was established by using lipopolysaccharide-stimulated RAW264.7 cells. Western blot- ting was used to detect the protein expression levels of SOCS1, JAK2, STAT3, and VDR. Reverse transcription-quantitative polymerase chain reaction was used to measure the mRNA expression of SOCS1, miR-222-3p, and VDR. An enzyme-linked immunosorbent assay was performed to measure the levels of inflammatory cytokines. A luciferase assay assessed the binding of SOCS1 to miR-222-3p. A total of 15 patients with ulcerative colitis and 18 healthy controls were recruited. The expression levels of SOCS1 and miR-222-3p in the colonic mucosa tissues of patients with ulcerative colitis and healthy controls were determined by reverse transcription-quantitative polymerase chain reaction. Results: SOCS1 upregulation inhibited the lipopolysaccharide-induced inflammation in RAW264.7 cells. SOCS1 was confirmed to be tar- geted by miR-222-3p. Silencing SOCS1 significantly abolished the inhibitory effects of miR-222-3p downregulation on inflammation. MiR-222-3p activated STAT3 signaling and reduced VDR expression by targeting SOCS1 in lipopolysaccharide-treated RAW264.7 cells. Additionally, miR-222-3p expression was upregulated in ulcerative colitis patients (P = 5.16E−10), while SOCS1 (P = 2.75E−10) and VDR (P = 52.5E−9) expression was downregulated in ulcerative colitis patients. Endoscopic scores (UCEIS) revealed significant positive cor- relation with miR-222-3p and negative correlation with SOCS1 and VDR. Conclusion: MiR-222-3p targets SOCS1 to aggravate the inflammatory response by suppressing VDR and activating STAT3 signaling in ulcerative colitis. Cite this article as: Xia F, Bo W, Ding J, Yu Y, Wang J. MiR-222-3p aggravates the inflammatory response by targeting SOCS1 to activate STAT3 signaling in ulcerative colitis. Turk J Gastroenterol. 2022;33(11):934-944.